Taking stock of national agricultural R&D capacity in Africa south of the Sahara - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2014)
This report is timely input into the ongoing development agenda for Africa South of the Sahara (SSA). The 2013 report on agriculture and food systems by the United Nations’ Sustainable Development Solutions Network released a set of post–2015 development goals, including recommendations that lowand middle-income countries increase their spending on agricultural research and development (R&D) by a minimum of 5 percent per year during 2015–2025, and that they allocate at least 1 percent of their agricultural gross development product (GDP) to public agricultural R&D.1 More recently, the Science Agenda for Agriculture in Africa was adopted at the African Heads of State Summit, necessitating the development of a continent-wide implementation plan. This report, which summarizes SSA’s recent progress in developing its national agricultural R&D systems, is intended to serve as an important input into, and potential benchmark for, the implementation of the science agenda in SSA and the broader development agenda for the region.